The Ginevra de’ Benci Effect: Competence, Morality, and Attractiveness Inferred From Faces Predict Hiring Decisions for Women - Menegatti, Michela; Pireddu, Sara; Crocetti, Elisabetta; Moscatelli, Silvia; Rubini, Monica (Frontiers in Psychology, 2021)
The present study examined the role of morality, competence, and attractiveness as perceived from faces in predicting hiring decisions for men and women. Results showed that for both female and male applicants, facial competence significantly predicted the hiring decision directly and indirectly, through the mediation of the overall impression. Decisions concerning female applicants were, however, significantly predicted by multiple dimensions – that is facial morality, facial competence, and attractiveness – with the mediation of the overall impression. Facial competence was the only significant predictor of impression and, in turn, hiring decision about men. These findings resonate the motto Virtutem forma decorat, “Beauty adorns virtue”, painted by Leonardo da Vinci on the reverse side of the portrait of Ginevra de’ Benci, and suggest that women’s chances of getting a job are less than those of men whenever they do not show a moral and competent and attractive face.